1998
DOI: 10.1155/1999/27037
|View full text |Cite
|
Sign up to set email alerts
|

Do Alterations in the Rate of Gastric Emptyingafter Injection Sclerotherapy for OesophagealVarices Play any Role in the Developmentof Portal Hypertensive Gastropathy?

Abstract: Bleeding from portal hypertensive gastropathy (PHG) has been estimated to account for upto 30% of all upper gastrointestinal haemorrhage in patients with cirrhosis and portal hypertension. Although portal hypertension seems to be an essential prerequisite, the precise mechanisms responsible for the development of PHG are unknown. The aim of this study was to examine the role of injection sclerotherapy of oesophageal varices in the development of PHG. Gastric emptying was studied using a radionuclide test meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Data on which technique of endoscopic variceal eradication leads to quantitatively more de novo PHG is contradictory. Most studies showed no differences in frequency or severity of PHG after variceal ligation vs sclerotherapy [19,34,41,73,92,93] , but some studies showed worse outcomes after variceal ligation [82,93,94] , while some other studies showed worse outcomes after sclerotherapy [95] .…”
Section: Esophageal Variceal Eradicationmentioning
confidence: 99%
“…Data on which technique of endoscopic variceal eradication leads to quantitatively more de novo PHG is contradictory. Most studies showed no differences in frequency or severity of PHG after variceal ligation vs sclerotherapy [19,34,41,73,92,93] , but some studies showed worse outcomes after variceal ligation [82,93,94] , while some other studies showed worse outcomes after sclerotherapy [95] .…”
Section: Esophageal Variceal Eradicationmentioning
confidence: 99%
“…A recent study suggested that autonomic neuropathy (AN) contributes to the formation of gallstones in patients with advanced cirrhosis (4). Acceleration, delay, or no significant change in gastric emptying in patients with cirrhosis was reported by a number of studies (5)(6)(7)(8)(9). AD seems to affect biliary motility directly through the neural pathway and/or indirectly through the probable effect of alteration in gastric emptying on CCK secretion.…”
Section: Introductionmentioning
confidence: 97%
“…Balan et al . [ 11 ] observed that the gastric emptying was disturbed in patients with portal hypertension and received sclerotherapy, which may contribute to portal hypertensive gastropathy. Gastroparesis in patients with liver cirrhosis may be due to autonomic dysfunction, which correlated positively with delayed gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 25 26 ] A delay in gastric emptying in patients with portal hypertension can aggravate or lead to the development of portal hypertensive gastropathy due to the deleterious effects of endogenous substances, such as acid and pepsin. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%